2013
DOI: 10.1016/j.seizure.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Cortical excitability in drug naive juvenile myoclonic epilepsy

Abstract: The study is suggestive of the existence of impaired supraspinal/intracortical inhibitory circuits which may account for the hyperexcitability of the motor system being prominent in the morning among drug naïve patients with JME. In this study, increased activity of cortical inhibitory networks, as evidenced by prolonged cortical silent period existed among drug naïve JME patients, but was found to be significant only in female patients. This may explain the increased seizure susceptibility in this cohort, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 49 publications
1
29
0
2
Order By: Relevance
“…These observations are in line with the recently proposed construct of 'system epilepsies' [16] and set JME as an archetype within this conceptual scheme. However, Puri et al [17] did not detect reduced CMT in 30 drug-naïve JME patients. These inconsistent results in well characterized IGE cohorts and in the absence of confounding factors, such as AED intake, are probably related to the small magnitude of the threshold decrease and the precision of threshold measurements.…”
Section: Key Pointsmentioning
confidence: 90%
“…These observations are in line with the recently proposed construct of 'system epilepsies' [16] and set JME as an archetype within this conceptual scheme. However, Puri et al [17] did not detect reduced CMT in 30 drug-naïve JME patients. These inconsistent results in well characterized IGE cohorts and in the absence of confounding factors, such as AED intake, are probably related to the small magnitude of the threshold decrease and the precision of threshold measurements.…”
Section: Key Pointsmentioning
confidence: 90%
“…Recent studies confirm JME is an epilepsy also profoundly affected by circadian rhythms [83]: myoclonic jerks and photosensitivity in JME are more likely to occur in the early morning, and are enhanced by sleep deprivation [83,84]; rates of IEDs were highest between one hour prior to the final awakening and the first 30 minutes after awakening [85]; and cortical excitability measured using transcranial magnetic stimulation (TMS) was higher in the morning in IGE, especially those with JME [86][87][88][89].…”
Section: Emerging Field Of Chronobiology Being Applied To Epilepsymentioning
confidence: 99%
“…Akgun et al 29 showed higher MTs and longer cortical silent periods (CSPs) in JME patients. This was supported by Puri et al 30 where prolonged CSP characterized JME group. High MTs were proposed to be related to antiepileptic therapy.…”
Section: Juvenile Myoclonic Epilepsymentioning
confidence: 59%